THE ROLE OF INTERACTIVE METHODS IN IMPROVING STUDENTS’ COMMUNICATIVE COMPETENCE IN ENGLISH LANGUAGE TEACHING (International journal of artificial intelligence, 2026)
This article explores the significance of interactive teaching methods in enhancing students’ communicative competence in English language education. In the context of modern educational reforms, the development of learners’ speaking, listening, and critical thinking skills has become a priority. The study analyzes the effectiveness of student-centered approaches such as group work, role play, project-based learning, and the integration of digital technologies. The article also discusses the pedagogical benefits of interactive methods, including increased motivation, learner autonomy, and active classroom participation. The findings indicate that the systematic use of interactive strategies leads to improved language proficiency and greater learner engagement.